2012
DOI: 10.1093/infdis/jir834
|View full text |Cite
|
Sign up to set email alerts
|

Protective Antigen Antibody Augments Hemodynamic Support in Anthrax Lethal Toxin Shock in Canines

Abstract: PA-mAb may augment conventional hemodynamic support during anthrax LT-associated shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Circulating ET in these patients could have contributed to this shock by causing arterial relaxation directly as well as by inhibiting the vasoconstrictor action of endogenous or therapeutically administered catecholamines. Possibly consistent with this, in a sedated and mechanically ventilated canine model, a regimen of fluid and norepinephrine support, which improved survival in LT-challenged animals, was ineffective with a similarly lethal ET challenge (3,34).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Circulating ET in these patients could have contributed to this shock by causing arterial relaxation directly as well as by inhibiting the vasoconstrictor action of endogenous or therapeutically administered catecholamines. Possibly consistent with this, in a sedated and mechanically ventilated canine model, a regimen of fluid and norepinephrine support, which improved survival in LT-challenged animals, was ineffective with a similarly lethal ET challenge (3,34).…”
Section: Discussionmentioning
confidence: 71%
“…In initial experiments, pretreatment with ET but not LT inhibited the contractile response of aortic rings to phenylephrine (PE) stimulation. In subsequent experiments directed at ET, we examined whether PA-directed monoclonal antibody (mAb) or adefovir, a nucleoside that selectively blocks EF-stimulated cAMP production, inhibited the effects of the toxin and whether ET's relaxant effects required an intact arterial endothelium (3,36,37). Also, to determine whether ET reverses catecholamine-induced arterial contraction, we measured its relaxant effects on aortic rings precontracted with PE.…”
mentioning
confidence: 99%
“…27,42 While antimicrobials prevent bacterial replication, they do not prevent the uptake of toxin and the subsequent formation of toxin complexes. 18,46,48,52 There is a biologically plausible conceptual basis to support antitoxin use in addition to antimicrobial therapy—to prevent intracellular uptake of circulating toxin. Antitoxin appears safe and well tolerated, 18,32,52 and thus the benefits appear to outweigh the risks.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study investigating the efficacy of norepinephrine treatment also showed that while norepinephrine improved survival of rats challenged with LPS and increased blood pressure before the onset of lethality with LT, it did not improve survival with the latter [87]. In contrast to these rat studies, however, in a mechanically ventilated canine model, conventional hemodynamic support (i.e., fluids and norepinephrine titrated on the basis of intravascular hemodynamic measures) did improve outcome [88]. Interestingly, the protective effects of hemodynamic support were enhanced when combined with anti-PA directed monoclonal antibody.…”
Section: Managementmentioning
confidence: 99%